Challenges on the diagnostic approach of inherited platelet function disorders: Is a paradigm change necessary?. (17th February 2018) - Nava, Tiago; Rivard, Georges-Etienne; Bonnefoy, Arnaud
Abstract: Inherited platelet function disorders (IPFD) have been assessed for more than 50 years by aggregation- and secretion-based tests. Several decision trees are available intending to standardize the investigation of IPFD. A large variability of approaches is still in use among the laboratories across the world. In spite of costly and lengthy laboratory evaluation, the results have been found inconclusive or negative in a significant part of patients having bleeding manifestations. Molecular investigation of newly identified IPFD has recently contributed to a better understanding of the complexity of platelet function. Once considered "classic" IPFDs, Glanzmann thrombasthenia and Bernard–Soulier syndrome have each had their pathophysiology reassessed and their diagnosis made more precise and informative. Megakaryopoiesis, platelet formation, and function have been found tightly interlinked, with several genes being involved in both inherited thrombocytopenias and impaired platelet function. Moreover, genetic approaches have moved from being used as confirmatory diagnostic tests to being tools for identification of genetic variants associated with bleeding disorders, even in the absence of a clear phenotype in functional testing. In this study, we aim to address some limits of the conventional tests used for the diagnosis of IPFD, and to highlight the potential contribution of recent molecular tools and opportunities to rethink the way we should approach the investigation of IPFD.